Effect of N, P, K and Mg fertilizers on some vegetative and generative parameters of a sweet cherry cultivar - Csihon, Á.; Gonda, I.; Orosz-Tóth, M.; Kincses, S.-né; Holb, I. J. (International Journal of Horticultural Science, 2020)
This two-year-study was aimed to provide results on the effect of nitrogen, phosphorus, potassium and magnesium fertilizer treatments (control, NP, NPK, NPKMg) on vegetative and generative features of the sweet cherry cultivar ‘Carmen’. Examinations were performed in an orchard planted in 2012 on Prunus mahaleb rootstock with spacing of 5 x 2.5 m. All treatments improved the vegetative features of the sweet cherry trees in both years of 2016 and 2017. Fertilizer treated trees increased trunk cross section area (TCSA) with 51.3-63.1%, while control trees showed 48.3% trunk growth increase. Yields of control trees were lower in both years (5.9-7.2 kg/tree), than that of the fertilized trees (7.8-11.3 kg/tree). Treatments also increased the phosphorus (16-22%), magnesium (12-20%) and potassium content (3.5-18%) of the fruits compared to control treatments.